A feasibility study on SurpRICE the healthy rice meal to-go - Dimaculangan, Mary Grace M.; Nilooban, Joan V.; Tardeo, Dacia Marisse P.; Villapando, Gina (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
This paper presents a feasibility study on SurpRICE, the healthy rice meal to-go. Specifically, it aims to verify the market, technical and financial feasibility of establishing and operating a restaurant that serves healthy and convenient rice meal presented in a unique way. It also seeks to establish the organization and management and social profitability of the said project. The product, hereafter referred to as SurpRICE, is a glutinous steamed, fried or flavored rice ball (or any shape) stuffed with viand as filling. The market feasibility phase of the study was initially conducted by describing the product concept, specifically the characteristics and features of SurpRICE. The market area was then selected. The chosen area is the National Capital Region primarily because the expected consumers of SurpRICE are concentrated here. Market survey was conducted to these consumers in order to encapsulate their preferences. Secondary data such as income and expenditure data were also gathered. Demand analysis was subsequently conducted to identify positive and negative factors which may influence buying, spending for and consumption of SurpRICE. Negative determinants were provided with solutions. The demand for SurpRICE was also estimated by benchmarking the demand for Paotsin, a small food establishment located in SM Megamall, which sells rice meals to-go and offers dine-in and takeout services. The primary customers of Paotsin are employees who work in nearby Ortigas Center and SM Megamail itself. Industry analysis was then carried out through the Porter's Five Forces Analysis. Competitor analysis was also done by identifying SurpRlCE's top competitors and describing their resources and capabilities. The competitive advantages of SurpRICE were also defined. A SWOT Analysis was then made to identify the strengths and weaknesses of SurpRICE and the opportunities and threats that its external environment poses. Market segmentation was subsequently carried out using four variables, namely geographic concentration, customer type, buying situation and demography. The target markets were then selected based on their willingness and ability to buy SurpRICE. Selective specialization strategy was then proposed to reach the target markets. Marketing strategies in terms of product and service, price, place and promotions were also formulated. Product and service strategies include brand strategy or the creation of a name recall for SurpRICE and its variants. Different product and service variants were also incorporated in order to cater to a large pool of consumers. Unique packaging concept and design were also presented. Pricing strategy was developed using penetration and psychological pricing. Penetration pricing shall be utilized during SurpRlCE's introduction stage while psychological pricing shall be employed when SurpRICE has already gained market stability. Place strategy was planned by deciding the distribution channel, which shall be a brick-and-mortar restaurant that shall be located at or near a business or school concentration area so that it would be close to its primary potential consumers. The restaurant shall also be classified as a fast-casual restaurant. The physical configuration of the restaurant was then described in terms of the areas of the restaurant especially the dining areas and of other conspicuous strategies. Promotions strategies were also conceptualized in relation to advertising which shall make use of flyers, tarpaulins, signage and digital advertisements. Public relations and publicity strategies in the form of event sponsorships and food booths on campuses, and tie-ups with companies for catering services during corporate promotional activities were also presented. Sales promotions strategies such as discount and free item coupons and "Special SurpRICEs" were likewise described. Consumer promotions were also developed in terms of "sulit meals", "bucket meals", other bundling strategies and free taste activities. The marketing plan of the restaurant for its first five years of the operation was then formulated. Finally, the revenue was forecasted. For the technical feasibility phase of the study, the menu of the restaurant was presented. The restaurant hours and service requirements were then determined. The materials needed by the restaurant were subsequently identified. These are the ingredients, packaging materials and supplies. The supply availability of the materials was then assessed. Specific sources of the said items were also named. The business processes of the company were also detailed. Procurement process was presented in terms of the systems for the purchasing of materials. Material Requirements Planning shall be used in determining the purchase quantity of or purchase interval for the material goods that comprise the SurpRICE product package while Lot-Sizing for Dynamic Demand shall be employed in scheduling the procurement of these material goods. The strategies for the procurement of materials were also defined using the Purchasing Portfolio Matrix. The production process was then described in terms of the preparation, cooking, designing and packaging activities for SurpRICE. A detailed example on how to mould and stuff SurpRICE was also presented. The planning process was subsequently discussed through inventory management of materials, forecasting of product demand and standardization of order processing operations. The distribution process was also illustrated through the different services of the restaurant. Ingredient, packaging material and service supplies requirements of the different SurpRICE products were also identified. Procedures for estimating the inventory requirements of the products and materials were provided. Equipment requirements were also enumerated. Capacity planning was subsequently conducted by establishing the dining capacity of the restaurant using peak demand. Allocations for ingredients, packaging materials and service supplies were then itemized. Minimum spoilage was also planned for using Material Requirements Planning. Manpower requirements were then estimated. The responsibilities of the employees were defined. The SurpRICE production plan was also detailed. Production rate was estimated. Production and target capacities were then compared. The equipment plan was also described. The site of the restaurant was subsequently selected using Factor Rating Method. The conditions prevailing in the chosen site were described. The required facilities systems were detailed. Interior design in terms of color and design and furniture and decorations were also described. The space requirements of the different areas of the restaurant were then estimated. The total space requirement was also computed. The layout of the restaurant was also created. Finally, investment and operating costs for the entire first year of the restaurant's operation were estimated. The total project cost was also estimated. For the organizational and management study, the name, mission and vision of the company were conceptualized. The form of organization was decided. The restaurant shall be of the general professional partnership type. Procedures for registering the company were listed. The responsibilities of the employees were defined. Training, work hours and days, and compensation and benefits were also detailed. For the financial feasibility phase of the study, the results of the market and technical feasibility studies were summarized. The project cost estimates of fixed assets, pre-production capital expenditures and working capital requirements were indicated. The available forms of financing were also identified. The start-up cost shall be generated from equity while operating cost for three months shall be loaned from a bank. Tax considerations were not included since the tax obligation of a general professional partnership is passed on to the partners. The pro-forma income statement, cash flow projections and pro-forma balance sheet for the first five years of the restaurant's operation were also presented. Profitability ratios such as return on assets and return on equity, the operating efficiency measure of asset turnover and financial leverage ratio of debt-equity ratio were computed. Liquidity/solvency measure of current ratio and breakeven selling price and volume were also calculated. The net present value, internal rate of return, and payback period for the project were then computed. In conclusion, the project is financially feasible as it passed all profitability tests. For the social profitability study, the tangible benefits of the study were identified and quantified. These include the improvement of the standard of living, personal income tax remitted to the government and patronage of local businesses. The intangible economic benefits were also described. These are environmental protection and sustainability and promotion of the Filipino culture.
Feasibility study.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Restaurants -- Philippines; Feasibility studies